Inventory Control of Grinding Mills Using Bearing Pressure Measurement - D. J. Oswald; J. G. Ziegler (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1974)
It is of common knowledge that loading within a grinding mill, whether ball, rod, pebble, or autogenous, is directly related to the lubrication back pressure developed between the mill journal and bearing shoe during mill operation. The merits of both forced-feed and gravitational-feed bearing lubrication methods are discussed with particular emphasis directed toward their applicability to continuous grinding mill inventory control. Data obtained from wet grinding mill applications in the cement and mining industries is presented to more clearly define the influence of such variables as feed consistency, slurry viscosity, mill retention, bearing oil temperature, grind fineness, and grinding media wear on the measured journal lubrication back pressure during automatic mill feed control. Finally, various grinding mill control schemes for maintaining constant mill loading and consequently optimizing mill operating efficiency are discussed and evaluated as to their advantages and/or disadvantages.